Mrs. Kennedy : the missing history of the Kennedy years - Leaming, Barbara (New York : Free Press, 2001)
A portrait of Jacqueline Kennedy during the thousand days of JFK's administration sheds new light on her life as both a woman and as First Lady, revealing the world of a woman fighting for herself, her marriage, and her husband's presidency
Includes bibliographical references (p. [365]-392) and index
Keywords: Onassis, Jacqueline Kennedy, -- 1929-1994; Presidents' spouses -- United States -- Biography; United States -- Politics and government -- 1961-1963